Signaling via the Interleukin-10 Receptor Attenuates Cardiac Hypertrophy in Mice During Pressure Overload, but not Isoproterenol Infusion - Stafford, Nicholas; Assrafally, Farryah; Prehar, Sukhpal; Zi, Min; De Morais, Ana M.; Maqsood, Arfa; Cartwright, Elizabeth J.; Mueller, Werner; Oceandy, Delvac (Frontiers in Pharmacology, 2020)
Inflammation plays a key role during cardiac hypertrophy and the development of heart failure. Interleukin-10 (IL-10) is a major anti-inflammatory cytokine that is expressed in the heart and may play a crucial role in cardiac remodeling. Based on the evidence that IL-10 potentially reduces pathological hypertrophy, it was hypothesized that signaling via the IL-10 receptor (IL10R) in the heart produces a protective role in reducing cardiac hypertrophy. The aim of this study was to investigate the effects of the ablation of Il-10-r1 gene during pathological cardiac hypertrophy in mice. We found that IL-10R1 gene silencing in cultured cardiomyocytes diminished the anti-hypertrophic effect of Il-10 in TNF-α induced hypertrophy model. We then analyzed mice deficient in the Il-10-r1 gene (IL-10R1-/- mice) and subjected them to transverse aortic constriction or isoproterenol infusion to induce pathological hypertrophy. In response to transverse aortic constriction for 2 weeks, IL-10R1-/- mice displayed a significant increase in the hypertrophic response as indicated by heart weight/body weight ratio, which was accompanied by significant increases in cardiomyocyte surface area and interstitial fibrosis. In contrast, there was no difference in hypertrophic response to isoproterenol infusion (10 days) between the knockout and control groups. Analysis of cardiac function using echocardiography and invasive hemodynamic studies did not show any difference between the WT and IL-10R1-/- groups, most likely due to the short term nature of the models. In conclusion, our data shows that signaling via the IL-10 receptor may produce protective effects against pressure overload-induced hypertrophy but not against β-adrenergic stimuli in the heart. Our data supports previous evidence that signaling modulated by IL-10 and its receptor may become a potential target to control pathological cardiac hypertrophy.